A compact calorimeter based on a magnetically insulated faraday cup for intense ion beam diagnostic; Известия вузов. Физика; Т. 55, № 10, ч. 3 - Pushkarev A. I. Aleksandr Ivanovich (2012, 2012)
Заглавие с экрана